Does the time frame between exercise influence the effectiveness of hydrotherapy for recovery? - Halson, S. L. (International Journal of Sports Physiology and Performance, 2011)
An increase in research investigating recovery strategies has occurred alongside the increase in usage of recovery by elite athletes. Because there is inconsistent evidence regarding the benefits of recovery on performance, it is necessary to examine research design to identify possible strategies that enhance performance in different athlete settings. The purpose of this review is to examine available recovery literature specifically related to the time frame between performance assessments to identify considerations for both research design and practical use of recovery techniques.